Calcined Waste Marsh Clam Shell in Various Combustion Temperatures as Phosphate Removal in Water - Muslim, Nur Husna; Maryani, Abdul Aziz; Hisham, Nur Aqilah; Mohd Radzi, Muhammad Ariff Aiman; Abdullah, Noorul Hudai; Abdul Salim, Nur Atikah; Abu Hassan, Norzainariah (International Journal of Integrated Engineering, 2024)
Phosphate is one of the major pollutants in water that might cause eutrophication in the receiving bodies of water. Excessive phosphate can stimulate algae blooms and deteriorate the water ecosystem’s quality. Many techniques focus on phosphate removal by using biological, physical, or chemical treatments. However, the application of the adsorption mechanism using calcined marsh clam shells (CMCs) has not yet been fully investigated in terms of various calcination temperatures. Hence, the ability of CMCs calcined at different temperatures were investigated to determine their potential to remove phosphate from aqueous solutions. The adsorbent materials were calcined at four different temperatures: 500, 600, 700, and 800 °C. In the batch experiment, 2 g of mass of absorbent in the size range of 1.18–2.36 mm mixed with 100 mL of solution. The physical and chemical properties of adsorbents were characterised to determine the surface morphology, functional groups, and elemental composition. The calcination temperature of 600 °C resulted the most effective adsorbent for phosphate removal (99.53%). Kinetic (pseudo-first-order and pseudo-second-order) and isotherm (Freundlich and Langmuir) models were applied to identify the adsorption mechanisms. The data fitted well to the pseudo-second-order kinetic model, indicating that the process is a chemical sorption process. The Freundlich isotherm model described the phosphate adsorption onto CMCs well, which indicates multilayer adsorption of phosphate on the CMCs surface layer. Overall, applying the different types of CMCs can enhance phosphate removal due to the capability of adsorption on surface materials and advanced understanding of the data verified using kinetic and isotherm models.